2009
DOI: 10.1002/job.635
|View full text |Cite
|
Sign up to set email alerts
|

Citizenship under pressure: What's a “good soldier” to do?

Abstract: SummaryOrganizational citizenship behaviors (OCBs) are typically defined as discretionary behaviors that contribute to the effective functioning of organizations. Prior research has generally focused on instances in which employees willingly engage in such behaviors; however, because OCBs are often informally encouraged and rewarded, workers may experience pressure to be ''good soldiers'' within their organizations. Using a sample of 245 employees, our findings indicate that citizenship pressure is related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
340
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(363 citation statements)
references
References 65 publications
(82 reference statements)
17
340
2
4
Order By: Relevance
“…The negative sign of beta coefficient for gender shows that married academic staff has a lower tendency to perform an OCB. This result is consistent with the empirical evidence documented by Bolino et al (2010). In spite of age, when the academic staff become older they tend to demonstrate a high level of OCB.…”
Section: Methodssupporting
confidence: 91%
“…The negative sign of beta coefficient for gender shows that married academic staff has a lower tendency to perform an OCB. This result is consistent with the empirical evidence documented by Bolino et al (2010). In spite of age, when the academic staff become older they tend to demonstrate a high level of OCB.…”
Section: Methodssupporting
confidence: 91%
“…Hence, it can be deduced that employees are not motivated to perform OCB due to negative feelings towards colleagues or the organization if they perceive the workplace as political (Hsiung et al, 2012). However, they feel obliged to perform OCBs as a tool to survive in the workplace because as Bolino et al (2010) mentioned that managers are encouraging OCB by means of organizational norms and culture, employee performance evaluation, and stories that highlight the expected beyond-duty behavior (OCB). While there can be a direct pressure on employees for engaging in OCB such as a job demand, there can be also indirect pressures such as social and organizational so that employees feel pressured to perform OCB in order to survive in the political work environment.…”
Section: 3organizational Politics Perception As An Antecedent Of Cmentioning
confidence: 99%
“…Then, this question has risen: What kind of pressure is that? OCB is investigated from the positive side such as its positive image, its constructive implications, its contribution to individuals and organizations at multiple levels, and its general reinforcement of performance in the workplace till today but in recent years, the assumptions behind the concept are started to question and there are growing studies (Bolino, Klotz, Turnley & Harvey, 2013;Bolino, Turnley, Gilstrap & Suazo, 2010;Bolino, Turnley & Niehoff, 2004;Gadot, 2006;Salamon & Deutsch, 2006;Zhao, Peng, Han, Sheard & Hudson, 2013;Zhao, Peng & Chen, 2014) which have examined OCB from a different perspective focuses on internal or external pressures on employees for exhibiting those behaviors. Gadot (2006) has proposed that OCB can arise from other motives, some of them less voluntary or less self-initiated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evidence for the positive organizational and individual outcomes of OCB (Podsakoff, Whiting, Podsakoff, & Blume, 2009) and the negative outcomes of CWB (Rogers & Kelloway, 1997) exists; other research has suggested that OCB emerges from non-positive motives (Bolino, Turnley, & Niehoff, 2004), has negative consequences for individuals (Bolino, Turnley, Gilstrap, & Suazo, 2010), and that CWB may sometimes be constructive (Galperin & Burke, 2006). Currently, the evidence is more supportive of a multidimensional, difference nature to OCB and CWB.…”
mentioning
confidence: 99%